Towards a standard conceptual typology of public sector performance measurement. (2nd January 2017) - Alach, Zhivan
ABSTRACT: This article aims to enhance fundamental conceptualisation in performance measurement through the development of a standard conceptual typology of the field. Performance measurement is a common phenomenon in the worldwide public sector, and one that has attracted substantial academic attention. However, analysis has been hindered by confusing and inconsistent terminology, and a lack of clear and explicit classification schemes. The proposed typology is based on five explicit design considerations and three fundamenta divisionis . The typology produced has four elements: levels ; measures ; targets ; and actuals . These elements relate to the nature, specific aspect and state of performance phenomena. It is likely that a standard conceptual approach will have benefits for academic analysis, by clarifying language and conceptual definitions. It is also likely to have beneficial practical implications.